The many meanings of iconoclasm: Warrior and Christian temple-shrine destruction in late sixteenth century Japan - Strathern, A (Brill Academic Publishers, 2020)
The conversion of certain warlords in Kyushu, Japan, (1560–1580 CE) represents one of the most important breakthroughs for Christianity in the early modern world, and it was accompanied by striking acts of destruction of the local sacred sites and objects. Yet shrine and temple destruction had already become a relatively commonplace feature of warfare in this period of internecine struggle, exemplified by the activities of Oda Nobunaga. How was the iconoclasm of Christian converts interpreted in this context? This article is particularly concerned with the implications of iconoclasm for a raging struggle of “empirical religiosity” – in which Christians and their opponents argued about the immanent power of the gods and their capacity to take revenge on iconoclasts. It also suggests that prevailing Buddhist and Confucian discourses presented important limits to how damaging such empirical arguments were to local religion. These issues are also explored in relation to the case of the Christianizing Ōtomo house, and their relations with the important Usa Hachiman shrine.